Girls from Santa Catarina: losing your life to become a mother - Souza, Maria de Lourdes de; Burgardt, Diego; Ferreira, Luiz Alberto Peregrino; Bub, Maria Bettina Camargo; Monticelli, Marisa; Lentz, Haimée Emerich (Revista da Escola de Enfermagem da USP, 2010)
The Maternal Mortality Ratio (MMR) is an indicator that analyses the life conditions and care given to pregnant women, and indicates whether the constitutional rights related to life and health are being complied with. This study shows losses of lives among adolescent women associated with pregnancy, childbirth and the puerperal period, in the state of Santa Catarina between 1994 and 2005. It is an exploratory study of a quantitative nature. There were 72 maternal deaths in adolescents, 67% had a direct obstetric cause, 23% had an indirect obstetric cause and about 9% were classified as accidental or incidental. The Maternal Mortality Ratio in adolescents was high and most could have been prevented and its causes controlled. The identified situation shows an absence of quality health care. To reduce these deaths it is central that nursing action be combined with other professionals and other organized sectors of society.